The Effectiveness Of Ruqyah Therapy With Al-Qur'an Recitation in Controlling Auditory Hallucinations Due to Paranoid Schizophrenia in The Tanjung Room Of The Banjar City Regional Public Hospital - Rahmatulloh, Rian; Suhanda, Suhanda; El Haque, Iif Taufiq (Yayasan Inspirasi El Burhani, 2025)
Introduction: Schizophrenia is a serious mental disorder that requires special attention. Approximately 1% of the global population has experienced schizophrenia at some point in their lives. According to the 2023 Indonesian Health Survey (SKI), the prevalence of mental disorders in Indonesia reaches 630,827 individuals (Ministry of Health of the Republic of Indonesia, 2023). One of the most common symptoms in individuals with schizophrenia is hallucination, particularly auditory hallucinations. In West Java Province, the prevalence of schizophrenia cases is recorded as the highest among other mental disorders, at 5.2% according to data from the Health Office Objective: This case study aims for patients to be able to demonstrate and implement nursing care for individuals with auditory hallucinations through the application of Ruqyah therapy with recitation. Method: This study employs a descriptive analysis method with a research approach focused on cases of patients experiencing auditory hallucinations. Result: During the assessment phase, it was found that the patient often talked and laughed to themselves, which indicated auditory hallucinations. The nursing diagnosis established was sensory perception disturbance: auditory hallucinations. The interventions and implementations provided focused on strategies for managing sensory perception disturbances, with the primary intervention being the administration of Ruqyah therapy with recitation.